Evaluation Of Speed Effect On Dynamic Stall Based On Low And High Fidelity Aeroelastic Rotor Simulations - Richez, F.; Berhouni, I.; Bailly, J. (My University, 2025)
This paper aims at analyzing the effects of an increasing advance ratio on the stall characteristics of a helicopter rotor in forward flight. This numerical investigation is performed with both a low fidelity approach based on free wake model and a high fidelity approach based on CFD. The objective is twofold: first, evaluate the capability of the free wake approach in predicting stall, and second, describe the flow characteristics specific to stall at high advance ratio. The results show that the low fidelity approach correctly predicts the global trend of dynamic stall at both moderate ( = 0.35) and high advance ratio ( = 0.55), but underestimates the intensity of the airloads fluctuations induced by stall. An in-depth analysis of high fidelity results has highlighted the main phenomena associated with stall at moderate and high speeds, and in particular the important role played by wake dynamics.